Awake Mouse fMRI and Pupillary Recordings in the Ultra-High Magnetic Field - Zeng, Hang; Jiang, Yuanyuan; Beer-Hammer, Sandra; Yu, Xin (Frontiers in Neuroscience, 2022)
Awake rodent fMRI is becoming a promising non-invasive brain imaging module when investigating large-scale brain function given behavioral tasks. Previous studies have either applied sedatives during scanning or pre-treatment of anesthetics, e.g., isoflurane, to reduce the motion of animals, which could confound the brain function of “awake” states in rodents. Here, we have established a long training awake mouse fMRI-pupillometry paradigm/setup without the initial use of anesthesia. To validate the awake mouse fMRI platform, evoked BOLD-fMRI was performed to identify brain activation in the visual cortex, dorsal lateral geniculate nuclei, and superior colliculus. Furthermore, pupil signal fluctuation was investigated during scanning, showing a less dilated pupil after 5–8 weeks of intermittent training. Thus, using the awake mouse fMRI with real-time pupillometry provides a longitudinal functional mapping tool to study fully conscious mice.